Eugénisme et redressement de l’enfant délinquant en Colombie au début du xxe siècle : la maison de correction et école de travail Fontidueño - Iván Olaya Pelaez (Histoire, Médecine et Santé)
In the context of the medicalization of childhood in the early 20th century in Latin America, juvenile delinquency was defined as a social pathology, the result of physical, mental, and “social” diseases that could be transmitted through biological heredity. Both clinical and educational measures were deemed necessary to address this problem, perceived as sociobiological, by rehabilitating the delinquent child in order to reintegrate them into society as a “useful” individual. Eugenics, a scientific and socio-political movement, contributed to this process of medicalization. This article seeks to analyze the medicalization of juvenile delinquency in Latin America and examine the role of eugenics in this development. We take the case of the Fontidueño reform school in Colombia to demonstrate the influence of eugenic discourse on the methods of rehabilitating the criminal child and the connection between local practices and transnational discussions.